BA 223 - Principles of Marketing - Linn Benton Virtual College (2018)
This course will provide you with a general survey of the nature significance of scope of marketing. It emphasizes customers (marketing analysis and strategy); business marketing decisions in promotion, distribution and pricing; and control of marketing programs.